2001
DOI: 10.1067/mtc.2001.114632
|View full text |Cite
|
Sign up to set email alerts
|

Modified Glenn connection for acutely ischemic right ventricular failure reverses secondary left ventricular dysfunction

Abstract: Right ventricular ischemia-induced dilation resulted in acute impairment of left ventricular contractility and relaxation. A modified Glenn shunt attenuated the left ventricular dysfunction by limiting right ventricular dilation and restoring left ventricular cavity geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…66 These effects may be clinically relevant when the RV is volume unloaded by placement of a caval pulmonary shunt. Danton et al 67 showed experimentally that acute RV ischemia induced by coronary artery ligation induced LV dysfunction as measured by end-systolic elastance, a load-independent measure of LV contractility. LV dysfunction secondary to RV ischemia was reversed by the addition of a caval pulmonary shunt with restoration of LV end-systolic elastance.…”
Section: March 4 2014mentioning
confidence: 99%
“…66 These effects may be clinically relevant when the RV is volume unloaded by placement of a caval pulmonary shunt. Danton et al 67 showed experimentally that acute RV ischemia induced by coronary artery ligation induced LV dysfunction as measured by end-systolic elastance, a load-independent measure of LV contractility. LV dysfunction secondary to RV ischemia was reversed by the addition of a caval pulmonary shunt with restoration of LV end-systolic elastance.…”
Section: March 4 2014mentioning
confidence: 99%
“…8 Right ventricular preload reduction using a Glenn Shunt reduced RV volume and pressure, normalized the IVS position during diastole, and increased LV filling and ejection and systemic blood pressure. 8 In another RV infarct model using different loading conditions, the IVS was noted to paradoxically 'bulge' toward the RV free wall at the onset of ventricular systole (PVSM) causing an increase in RV dP/dt, a reduction in RV volume, and forward ejection of blood from the RV. 10,11,30 These authors speculated that the systolic pressure increase in the normally functioning LV was unopposed by the reduced pressure generation in the depressed RV, thereby increasing the left-to-right pressure gradient across the IVS.…”
Section: Lv-rv Interaction and The Ivsmentioning
confidence: 97%
“…[3][4][5][6] This left to right ''ventricular assistance'' is influenced by RV volume and pressure and the transseptal pressure gradient. 7,8 The clinical impact of this interaction increases with increasing RV dysfunction. [4][5][6][8][9][10][11] A number of investigations describe this interventricular interaction in terms of the IVS position, highlighting its impact on both LV and RV functions.…”
Section: Résumémentioning
confidence: 99%
See 2 more Smart Citations